REMINISCES OF "THE MASSES OF SPHERICAL GALAXIES M32, A LIKELY APPLICATION" BY POVEDA (1958) - Omar López-Cruz (Revista Mexicana de Astronomía y Astrofísica, 2011)
This article contains the elements in the form of an interview, where Poveda describes the gestation of thepaper ¿The Masses of Spherical Galaxies M32, a likely Application¿, 1958, BOTT, 2, 17, 3.